2014
DOI: 10.1080/03004430.2014.983916
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between creativity, social play, and children's language abilities

Abstract: In this study, we explore the interconnectedness between children's creativity, social play, and language abilities. The participants were 225 (109 girls, 116 boys) preschool children, from diverse European American, African American, and Hispanic ethnic heritages. We assessed the children in three ways. First, each child completed the Goodenough Harris Draw a Person task as a measure of creativity. Second, we recorded observations of children's social play using time sampling techniques and Howes and Matheson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…At the same time, they are processes that have an intrinsic value (FNAE, 2018, p. 58). A positive relationship has been proven between play and children's creativity (Holmes, Romeo, Ciraola, & Grushko, 2015;Russ, 2016;Russ & Dillon, 2011). Childreńs play promotes the affective and cognitive processes, which are critical in their creativity (Saracho, 2012, p. 18).…”
Section: Creativity In Ececmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, they are processes that have an intrinsic value (FNAE, 2018, p. 58). A positive relationship has been proven between play and children's creativity (Holmes, Romeo, Ciraola, & Grushko, 2015;Russ, 2016;Russ & Dillon, 2011). Childreńs play promotes the affective and cognitive processes, which are critical in their creativity (Saracho, 2012, p. 18).…”
Section: Creativity In Ececmentioning
confidence: 99%
“…According to Bateson (2014), the link of play to creativity and hence to innovation in humans is strong. Fostering creativity also enhances other competency and skills, such as language abilities (Holmes et al, 2015) and social skills (John, Cameron, & Bartel, 2016).…”
Section: Creativity In Ececmentioning
confidence: 99%
“…As far as play is concerned, children do not think that it is separate from their life careers but instead that it is a career for life. In other words, play to children is the same as work is to adults 37 . Children commit to play not because it is an easily done task but rather they enjoy it because it is challenging.…”
Section: Development Of Intellectual and Moral Functionmentioning
confidence: 99%
“…In addition, language development can be promoted through activities like drama, poetry, social play, watching video or listening to music (Nachiappan, 2015;Holmes et al, 2015;Holmes and Romeo, 2013;Meacham et al, 2013). Holmes and Romeo (2013) found that gender and administration of the preschool is a factor that influenced language abilities and students' social games.…”
Section: Literature Reviewmentioning
confidence: 99%